Determination of hygiene status of milk sold in Lahore, Pakistan - Fatima, Sonia; Zubair, Asim; Fatima, Huma; Ayesha, Ayesha; Tehreem, Ayesha (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
Although milk is a vital source of nutrients and energy, its safety depends heavily on sanitary handling, storage, and marketing procedures. This study used proximate analysis, microbial load estimation, and field-based hygiene assessments to examine the cleanliness state of raw milk sold in Lahore, Pakistan. In accordance with AOAC protocols, samples were gathered from two disparate urban areas (Iqbal Town and Gulberg) and examined for fat, protein, moisture, ash, acidity, total solids, and solids-not-fat content. The Methylene Blue Reduction Test (MBRT) and the Total Bacterial Count (TBC) were used to evaluate the microbiological quality. The majority of the samples did not meet Punjab Pure Food and Codex requirements, according to the data. According to MBRT results, just 13.3% of samples were good, 23.3% were fair, and 63.6% were of poor quality. In almost every instance, TBC levels were higher above allowable limits, suggesting a substantial danger of microbiological contamination. These findings were supported by field surveys, which showed that 80% of vendors sold milk in thin plastic bags that encourage bacterial growth and chemical contamination, 35% used containers that were not properly cleaned, and 65% of vendors had poor personal hygiene.  Pathogens including Salmonella, Listeria, and E. coli pose major health concerns to the population, and the lack of cold chain management further degraded milk quality. In order to guarantee milk safety and the welfare of consumers, the study emphasizes the critical need for more hygienic enforcement, better transportation and storage procedures, and awareness campaigns.